(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to evaluate our phytobezoar cases who were followed up and treated due to mechanical obstruction in our clinic.Materials and Methods: The files of acute abdomen or ileus patients who were followed up in the Elazığ Training and Research Hospital General Surgery Clinic between January 2013 and January 2018 were evaluated retrospectively. Patients whose data were not available and who were followed up and treated for non-phytobezoar ileus and acute abdomen were excluded from the study. Nine patients meeting the inclusion criteria were reviewed retrospectively. Demographic data (age, gender) of the patients, previous surgical histories, comorbidites, whether there is gastric or intestinal bezoar, treatment options and complications were recorded. Numerical data are given as median (minimum - maximum values); categorical data are given as n (%) for statistical evaluation.Results: Three of the patients were female (33.4%) and 6 were male (66.7%).The median age of all patients was 71(25–78) years. Seven of the patient had previous surgical intervention history (77.8%) (5 had gastric surgery and 2 had other abdominal surgery history), 2 (22.2%) had no previous surgical intervention history. Two of the patients (22.2%) whom endoscopic intervention was performed for with gastric bezoar, operated for intestinal obstruction due to migration of gastric bezoar.One of the patients (11.1%) whom had no surgical intervention history had primary intestinal bezoar and one (11.1%) had concomitant intestinal bezoar with gastric bezoar.Conclusion: Mechanical obstruciton due to bezoars, must be kept in mind in patients who had perivous gastric surgery history and habitual eating disorders.Not only the exploration of the target area but also whole exploration must be done.Close follow up for migration is important for the gastric bezoars after endoscopic interventions.